2022
DOI: 10.3233/wor-205095
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and dyslipidemia among primary health care professionals: A Cross-sectional study

Abstract: BACKGROUND: Cross-sectional studies point out important evidence between anxiety and dyslipdemic disorders in health workers. OBJECTIVE: Our main objective was to estimate the association between anxiety and dyslipidemia in Primary Health Care (PHC) nursing professionals in Feira de Santana, Bahia, Brazil. METHODS: A confirmatory cross-sectional study involving 376 PHC nursing professionals. Data collection occurred through the application of a questionnaire containing sociodemographic, labor and lifestyle iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…2). The study found a correlation between anxiety symptoms and dyslipidemia in MDD patients, consistent with previous research (19)(20)(21)(22)30). In contrast to previous ndings, there was no notable difference in anxiety symptom rates between the EAO and MAO groups.…”
Section: Clinical Correlates Of Anxiety Symptoms In Eao and Mao Groupssupporting
confidence: 91%
See 1 more Smart Citation
“…2). The study found a correlation between anxiety symptoms and dyslipidemia in MDD patients, consistent with previous research (19)(20)(21)(22)30). In contrast to previous ndings, there was no notable difference in anxiety symptom rates between the EAO and MAO groups.…”
Section: Clinical Correlates Of Anxiety Symptoms In Eao and Mao Groupssupporting
confidence: 91%
“…On the other side, comorbid anxiety in MDD patients are associated with many metabolic disorders(e.g.dyslipidemia, impaired glucose and hypothyroidism). Previous studies have revealed that anxiety is correlated to serum lipid abnormalities in MDD patients (19,20). A systematic review showed that patients with heterozygous familial hypercholesterolemia exhibited differences in anxiety symptoms and mental health compared with the general population (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant relationship was found between ldl and total cholesterol, which are associated with cvd risk, and work stress. As in our study, a study conducted in Brazil in 2022 found a positive relationship between anxiety and dyslipidaemia in primary healthcare nursing professionals [30].…”
Section: Discussionsupporting
confidence: 80%
“…Several studies have reported an association between abnormal blood lipid levels and anxiety ( 16 , 17 ). Although some studies have highlighted a possible association between dyslipidemia and anxiety, few studies have investigated the relationship between dyslipidemia and anxiety symptoms in patients with MDD.…”
Section: Introductionmentioning
confidence: 99%